2019
DOI: 10.4034/pboci.2019.191.108
|View full text |Cite
|
Sign up to set email alerts
|

Polymicrobial Leakage and Retention of MTA and Portland Cement in a Model of Apexification

Abstract: Objective: To evaluate the sealing capacity and retention of apical barriers made with mineral trioxide aggregate (MTA) and Portland cement (PC). Material and Methods: Fifty-six bovine incisors were sectioned 8 mm above and 12 mm below the cement-enamel junction. The root canal was enlarged with a diamond drill to create a standard 2.5 mm diameter opening. Apical sheets of 5 mm thickness were placed using white MTA-Angelus or white PC. Fifteen samples of each material were exposed to human saliva in a dual cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A previous research project evaluated the bacterial leakage of MTA over three time periods and found that 60-70% of specimens were sealed after 10 days, and then sealing ability reached 100% at 30 days [31]. This study investigated the nanoleakage of retrograde materials over five timepoints: on the 1st, 3rd, 7th, 15th, and 30th days.…”
Section: Discussionmentioning
confidence: 99%
“…A previous research project evaluated the bacterial leakage of MTA over three time periods and found that 60-70% of specimens were sealed after 10 days, and then sealing ability reached 100% at 30 days [31]. This study investigated the nanoleakage of retrograde materials over five timepoints: on the 1st, 3rd, 7th, 15th, and 30th days.…”
Section: Discussionmentioning
confidence: 99%
“…A previous research project evaluated the bacterial leakage of MTA over three time periods and found that 60-70% of specimens were sealed after 10 days, and then sealing ability reached 100% at 30 days [19].…”
Section: Discussionmentioning
confidence: 99%